Pengaruh Budaya Organisasi Terhadap Komitmen Organisasi yang di Mediasi Kepuasan Kerja - Sinta Sundari Heriyanti; Richnie Zayanti (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
For companies to have high competitiveness in the era of globalization, one of which needs to be considered in the field of human resources. This study focuses on organizational culture in implementing its performance through job satisfaction. In the current era of globalization, competitiveness between companies has been so complex that it is no longer possible for companies to ensure that companies continue to exist in the business world. The purpose of this study was to determine whether there is an influence of organizational culture on the organizational commitment that mediates job satisfaction. The object of research at PT Nipro Indonesia, Karawang industrial area. The research was conducted using quantitative methods. The number of samples obtained using a random sampling technique using the Slovin formula is 57 respondents. The data was collected using a google form in filling out an online survey. The data analysis method used was the R-square test, Bootstrap, Path Coefficient, and specific indirect effects. The results of this study indicate that organizational culture does not affect organizational commitment, organizational culture affects job satisfaction, job satisfaction affects organizational commitment, job satisfaction can have a positive effect in mediating the relationship between organizational culture and organizational commitment at PT Nipro Indonesia.